The Effect of COVID-19 on Supply Chain Management of RMG Sector in Bangladesh - Jebin, Esrat; Hossain, Md. Faruque (AIUB Journal of Business and Economics, 2022)
Readymade garments (RMG) are the largest export earner for Bangladesh, starting from $31.57 million, has now boomed to $24 billion in fiscal year 2019-20. Although this is less than the previous year but still this sector is saving the total economy of Bangladesh. Amid the COVID-19 pandemic when the economy of the whole world on the edge, Bangladesh economy still trying to fight depending on apparel industry. Due to COVID-19 pandemic, many things are changed in this factor and we are still trying to figure out how we can cope up with the situation. The unprecedented pandemic effect of COVID-19 disrupted the entire supply chain of RMG sector. Along with it many more problems come in front which we ignored in the past. Decreasing lead time, over dependency on few countries for raw material, declining percentage female worker are some of these problems. Therefore, this study is an attempt to find out the effect of COVID-19 pandemic on the supply chain management of the RMG sector, consequence of this pandemic, steps taken by the garments owners and BGMEA, major problems the sector is facing, and solution of those problems. The research tool was questionnaire and interview scheduled for management and owners. Data was collected randomly from different levels of managements. The study divulged that garments owner are not happy with the changing attitude of international buyers. The BGMEA has been monitoring the situation from the beginning of the pandemic and now they are thinking of alternate option for raw materials and to create new business relationship. Concluding remarks, at the beginning, the industry was build based on wage competitiveness but now we have to be very strong with other components in order to survive. Wage competitiveness, compliance, lead time and supply chain these four are the pillar to be successful in this industry and now it is time to give equal importance on all of these.